Stakeholder engagement in a non-profit organisation: an issue-based perspective. (2019) - Heikkinen, Anna; Kujala, Johanna; Inha, Maria
The aim of this study is to gain insight into stakeholder engagement in a non-profit network organisation; it contributes to the literature on collaborative and cooperative understanding of stakeholder engagement by presenting an issue-based perspective of a non-profit organisation. The research is conducted as a qualitative case study, and multiple data sources are used to examine stakeholder engagement in the case organisation from two perspectives: 1) stakeholders and stakeholder relationships; 2) the issues and their salience as advocated by the stakeholders. It concludes that non-profit network organisations depend on their stakeholders for various resources. Because the continuation of a non-profit organisation is fully dependent on the support of its stakeholders, it can be viewed as an ultimate stakeholder organisation; here, joint activities create value for all parties involved, and the organisation practically exists through its stakeholders. These conclusions contribute to the stakeholder literature by extending the models to include non-profit organisations.